History and Relationship of Qur'an Verses to Rebo Wekasan Tradition at the Darul Ulum Islamic Boarding School in Banyuanyar, Pamekasan - Romziana, Luthviyah; Lutfi, Lutfi (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Rebo Wekasan is a tradition believed by the Indonesian people, especially the Madurese community, who believe that Allah sends calamities and diseases as many as 320,000 in a day. This study aims to discuss the origin of the Rebo Wekasan ritual tradition at Darul Ulum Banyuanyar Islamic Boarding School in Madura and the correlation of Quranic verses written in the Rebo Wekasan amulet with the history of Rebo Wekasan. This research used a qualitative method with a field approach located at Darul Ulum Banyuanyar Islamic Boarding School. The results show that this ritual originated with KH. Abdul Hamid bin Istbat, who performed the ritual, and then the students and the surrounding community followed his example until now. As for the correlation of Quranic verses with the history of Rebo Wekasan, the verses written in the amulet contain the meaning of salvation and a good reward for those who are patient in facing the given test.